2015
DOI: 10.1097/ogx.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolapse Meshes on the Metabolism of Vaginal Extracellular Matrix in Rhesus Macaque

Abstract: Objective-The impact of polypropylene mesh implantation on vaginal collagen and elastin metabolism was analyzed using a nonhuman primate model to further delineate the mechanism of mesh induced complications.Methods-49 middle aged parous rhesus macaques underwent surgical implantation of 3 synthetic meshes via sacrocolpopexy. Gynemesh PS (n=12) and two lower weight, higher porosity, lower stiffness meshes -UltraPro (n = 19) and Restorelle (n=8) were implanted, in which UltraPro was implanted with its blue orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…To prevent stress‐shielding and shear stress at the implant‐tissue interface, the implant should not be stiffer than the surrounding soft tissue . Healthy anterior vaginal wall tissue has stiffness 5.51 ± 0.36 MPa; which is close to what we observed in the Nylon nanofibrous matrices.…”
Section: Discussionsupporting
confidence: 80%
“…To prevent stress‐shielding and shear stress at the implant‐tissue interface, the implant should not be stiffer than the surrounding soft tissue . Healthy anterior vaginal wall tissue has stiffness 5.51 ± 0.36 MPa; which is close to what we observed in the Nylon nanofibrous matrices.…”
Section: Discussionsupporting
confidence: 80%
“…Liang et al . observed an increase in active MMPs including MMP-2 at 1 year after mesh implantation which means active remodelling persists after a long period of time28. A recent study showed that fibroblasts surrounding the mesh displayed a strong MMP-2 gene transcriptions whereas farther fibroblast had low MMP-2 synthesis rate29.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the degradable UPy-PC nor the non-degradable PU electrospun implants have been tested in an animal model for vaginal surgery. Therefore, we aimed to use the sheep model to evaluate these two materials and to compare the outcomes with a simulated native tissue repair (NTR) and implantation with a novel generation lighter-weighted PP, which has better biomechanical properties and yields a more favorable inflammatory response than other PP constructs [19][20][21]. Neither of the materials has been tested in the sheep model for vaginal surgery before.…”
Section: Introductionmentioning
confidence: 99%